Balancing Economic Opportunities And Security Risks In The Pakistan, Afghanistan, And Central Asia Corridor: Sosiology Law - Arief Fahmi Lubis (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This research explores the strategic and economic significance of the Pakistan–Afghanistan Central Asia corridor, a region historically linked by the ancient Silk Road and now positioned at the heart of modern connectivity initiatives such as China’s Belt and Road Initiative (BRI). While the corridor offers vast potential for trade, energy, and regional integration, it simultaneously faces persistent challenges of insecurity, political instability, and great power rivalry. The study examines whether economic integration can serve as a catalyst for peace or whether stability must first be secured to enable development. Drawing on economic, security, and geopolitical perspectives, the paper argues that peace and prosperity are mutually reinforcing rather than sequential goals. Projects such as TAPI and CASA-1000 demonstrate the potential of shared economic interests to promote cooperation; however, insecurity in Afghanistan and identity-based divisions continue to threaten progress. The analysis recommends an inclusive economic approach, a joint regional security mechanism, balanced engagement with major powers, and gradual, community-centered integration. Ultimately, sustainable peace in the corridor depends on parallel progress in both security and development. If managed wisely, the corridor can transform from a zone of tension into a platform for interregional cooperation and shared prosperity.